Efektivitas Penggunaan Whatsapp sebagai Media terhadap Hasil Belajar PAI di SMK Swasta LPMD Kabun - Angraini, Aminah; Aprison, Wedra (Lembaga Yasin AlSys, 2023)
The study aimed to discuss the effectiveness of using WhatsApp as a medium for PAI learning outcomes using report cards at LPMD Private Vocational Schools with a research population of class X TSM A and X AKT B SMK Private LPMD Kabun. The background of this research is to take student report card scores to find out how effective the use of WhatsApp is in PAI learning during this pandemic. Therefore, the researcher wants to find out how effective PAI learning outcomes are with the use of WhatsApp media. This research is to answer the problems (1) the effectiveness level of using WhatsApp as a learning medium for PAI learning outcomes at SMKS LPMD Kabun. This research is discussed in the form of quantitative research. This research was conducted at SMKS LPMD Kabun. Using data processing techniques in the form of documentation. Data were analyzed using the average and standard deviation formulas (standard deviations). This research shows that: (1) The learning outcomes of using WhatsApp in PAI learning at SMKS LPMD Kabun are generally in the Good category. The mean and standard deviation analysis found a positive or accepted relationship between the PAI learning outcomes in class X TSM SMKS and X AKT B LPMD Kabun.